Programmable graphene-based humidity and heat driven actuators prepared by one-step laser direct writing. (4th September 2019) - Shi, Jiaxin; Sun, Kai; Lv, Yuhuan; Li, Ruhao; Deng, Jianping; Wang, Chengzhong; Pan, Kai
Abstract: Smart materials are gathering increasing attention and play important roles in intelligent actuators, among which films with Janus structure are widely used because of their intrinsic response ability. Herein, we report a highly simplified method, laser direct writing, for preparing GO (Graphene Oxide)/rGO (Reduced Graphene Oxide) Janus films. By adjusting the output power of laser, GO homogeneous films can be accurately reduced in a single step and a certain thickness can be controllably reduced to form GO/rGO Janus films. The structure and chemical composition of the resulting GO/rGO films were characterized. Their response to ambient temperature and humidity is determined experimentally. The response performance of Janus films with different thickness was tested, and the one with thickness of 15 μ m performed the best. The Janus films are made into diverse actuators, including a bionic movable creeper and a grabber that can grab a leaf upon changing the humidity in a planned way. Furthermore, we designed a finger-guessing robot that can be programmed in advance and perform the predetermined actions.